Construction and Validation of a Scale to Measure Islamic Primary School Teachers’ Readiness in Implementing Emancipated Curriculum Referring to the Technological Pedagogical and Content Knowledge - Sarah, Siti; Suprihatiningrum, Jamil; Gunawan, Yosi Intan Pandini; Salam, Firman Walidi (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop and validate a scale to measure the readiness of science teachers in Islamic primary schools in implementing the Emancipated Curriculum referring to the Technological Pedagogical and Content Knowledge (TPACK). Eight development steps by DeVellis were used to develop the scale. A total of 224 respondents, comprising six experts and 218 science teachers in Central Java Province and the Special Province of Yogyakarta, agreed to participate. Data were analyzed using SEM-PLS. The development process successfully created a scale of 34 valid and reliable items. These items consist of Technological Knowledge factors (four items), Pedagogical Knowledge factors (14 items), Content Knowledge factors (four items), Pedagogical Content Knowledge factors (four items), Technological Content Knowledge factors (two items), Technological Pedagogical Knowledge factors (two items), and Technological Pedagogical and Content Knowledge factors (three items). A high reliability was obtained for the scale developed (0.983). This validated scale is ready to be used to examine teachers’ readiness in implementing the Emancipate Curriculum. The measurement with this scale can illustrate the extent to which teachers have TPACK as a provision for implementing the curriculum so that policy recommendations can be made.